2005
DOI: 10.1007/s11099-005-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Different responses to UV-B enhanced solar radiation in radish and carrot

Abstract: Radish (Raphanus sativus L.) and carrot (Daucus carota L.), plants with underground storage organs grown in the field, were exposed to either ambient (UVA) or 20 % UV-B (UVE) enhanced solar radiation till their root yield stage. In radish, UVE produced a significant increase in shoot and root fresh mass (FM), increase in the contents of chlorophyll, carotenoids, flavonoids, and total proteins per unit FM, Hill reaction rate, and root yield. In contrast, carrot responded negatively to UVE showing a loss in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…In addition to shoots, faba bean roots also responded to moderate UV-B by increasing flavonoid concentrations (Figures 1Á4), which is consistent with the phenomenon observed in A. thaliana (Tong et al 2008) and radish (Raphanus sativus) roots (Nithia et al 2005). Moderate UV-B application distinctly enriched the total flavonoid levels, as well as the levels of kaempferol, luteolin, and quercetin in both the shoots and roots of sole and in mixed cropped faba bean.…”
Section: Resultssupporting
confidence: 85%
“…In addition to shoots, faba bean roots also responded to moderate UV-B by increasing flavonoid concentrations (Figures 1Á4), which is consistent with the phenomenon observed in A. thaliana (Tong et al 2008) and radish (Raphanus sativus) roots (Nithia et al 2005). Moderate UV-B application distinctly enriched the total flavonoid levels, as well as the levels of kaempferol, luteolin, and quercetin in both the shoots and roots of sole and in mixed cropped faba bean.…”
Section: Resultssupporting
confidence: 85%
“…Such an effect relies on the biosynthesis costs of flavonoids and related phenolic compounds, which are generally higher than those of biomass [36]. Conversely, several authors have reported an increased plant biomass in response to moderate UV-B doses in faba bean [33], radish [37], and Arabidopsis [38]. A similar response was found in our work, where both top and root weights increased upon treatment (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…The analyses of environment effects on the overall accumulation level of secondary metabolites per sub-family (chlorogenic acids, flavones, mono- and sesquiterpenes) revealed statistical differences between the three environments studied (Angers tunnel, Blagon field and Ychoux field; Table 1 ). This has already been described in a very high number of papers where biotic or abiotic environmental factors are cited as responsible for fluctuations in the accumulation of plant secondary metabolites, even for the carrot species 33 , 36 39 . In the present study, the overall accumulation level of secondary metabolites could also be explained by a combination of different biotic and abiotic factors, however we were not able to distinguish one from the other, and the main focus of the present paper is genetics.…”
Section: Discussionmentioning
confidence: 80%